Human resources: development and utilisation - Sabhanayakam, S. (Delhi, 1988)
The book analyses varied theories of the economists on the subject Development and Utilization of Human Resources' (With special reference to India and Tamil Nadu). The demographic changes, predominance of rural population and the backwardness and indifference of the female population in develop mental efforts are highlighted in a logical and scientific way. An estimate is made about the size and ratio of female participation to total population in economically productive activities for examining the under-utilization of womanpower. Comparisons are also made with selected socialistic and capitalistic nations pertaining to female participation in productive activities. The study elucidates the low employment potential of the organised large industries and stresses the need for developing the small and village industries with the adoption of a modern and an intermediate technology. Issues of unemployment and under employment are discussed with reference to the theories propounded by economists. A strong emphasis is established for developing the decentralised or diversified sector in rural India to mitigate the evils of unemployment.
Keywords: Human capital - India